2009
DOI: 10.1111/j.1365-246x.2009.04281.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual ocean tide signals from satellite altimetry, GRACE gravity fields, and hydrodynamic modelling

Abstract: P>Improvements of a global state-of-the art ocean tide model are identified and quantified by applying three independent approaches, namely (i) empirical ocean tide analysis of multimission altimeter data, (ii) evaluation of GRACE data and gravity field models and (iii) high resolution hydrodynamic modelling. Although these approaches have different capabilities to sense ocean tides they obtain results which are basically consistent one with each other. The analysis of altimeter data clearly identifies signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…EOT11a [ Savcenko and Bosch , ] is the latest version of a series of global ocean tide models, derived at Deutsches Geodätisches Forschungsinstitut (DGFI) by means of empirical analysis of multimission satellite altimetry data. EOT11 is used for reprocessing of GRACE gravity data [ Bosch et al , ]; it is based on sea surface heights observed by Topex, Jason‐1, Jason‐2, ERS‐2, and Envisat over the ice‐free oceans covering altogether the period October 1992 to March 2010. Tidal constituents were estimated based on a residual least squares harmonic analysis with FES2004 taken as reference model.…”
Section: Summary Of Participating Tide Modelsmentioning
confidence: 99%
“…EOT11a [ Savcenko and Bosch , ] is the latest version of a series of global ocean tide models, derived at Deutsches Geodätisches Forschungsinstitut (DGFI) by means of empirical analysis of multimission satellite altimetry data. EOT11 is used for reprocessing of GRACE gravity data [ Bosch et al , ]; it is based on sea surface heights observed by Topex, Jason‐1, Jason‐2, ERS‐2, and Envisat over the ice‐free oceans covering altogether the period October 1992 to March 2010. Tidal constituents were estimated based on a residual least squares harmonic analysis with FES2004 taken as reference model.…”
Section: Summary Of Participating Tide Modelsmentioning
confidence: 99%
“…Data constraints were provided on a global grid using the EOT11a [ Savcenko and Bosch , ; Bosch et al ., ]) which is a state of the art tide empirical model, comparable in quality with the GOT model [ Ray , ], although the accuracy over shelves is far from perfect in both data sets. Corrections for the ocean tides were made relative to the FES2004 model.…”
Section: Constrained Hamtide Tidal Solutionmentioning
confidence: 99%
“…Ocean tide models are usually used to provide corrections to GPS, altimeter or gravity data, which can later be adopted for further studies, such as ice mass balance or GIA. The prediction accuracy of ocean tide models is essential since the improvement of tidal corrections can effectively and correctly remove the tidal 'noise', so that the nontidal signals of interest can be studied more reliably (Bosch et al 2009). Since the launch of T/P satellite, much progress in improving global tide models has been achieved (Fu et al 1994).…”
Section: Introductionmentioning
confidence: 99%